Circulating Soluble Lectin‐Like Oxidized Low‐Density Lipoprotein Receptor‐1 Levels Are Associated With Erectile Dysfunction in Patients Without Known Coronary Artery Disease. (22nd October 2012) - Kobat, Mehmet Ali; Fırdolas, Fatih; Balin, Mehmet; Çelik, Ahmet; Bentli, Recep; Baydas, Adil
ABSTRACT: Aim.  Endothelial dysfunction and microvascular damage are involved in the pathogenesis of erectile dysfunction (ED). Soluble lectin‐like oxidized low‐density lipoprotein receptor‐1 (sLOX‐1) is identified endothelial receptor for oxidized low‐density lipoprotein (ox‐LDL) that plays a pivotal role in ox‐LDL‐induced endothelial dysfunction. The purpose of the current study was to determine the association between sLOX‐1 and ED in patients without known coronary artery disease (CAD). Main Outcome Measures.  Diagnosis of ED was based on the International Index of Erectile Function Score‐5. Levels of sLOX‐1 were measured in serum by enzyme‐linked immunosorbent assay. Methods.  One hundred thirty‐eight subjects with ED patients without known CAD (ED group) and 75 age‐matched subjects without ED and known CAD (Non‐ED Group) were included in this study. Results.  Plasma levels of sLOX‐1 were significantly higher in ED than in Non‐ED group (95 ± 87 and 49 ± 30 pg/mL, respectively, P  < 0.001). The levels of sLOX‐1 highly negative correlated with score of ED (r = −0.618, P  < 0.001). The sLOX‐1 levels >75 pg/mL predicts ED with 26.8% sensitivity and 96.0% specificity on receiver operator characteristic analysis. Conclusions.  Our study demonstrated that serum sLOX‐1 levels were associated with endothelial dysfunction that predicts ED. Moreover, the current study revealed that there was strong negative correlation between the levels of circulating sLOX‐1 and score of ED. This study suggested sLOX‐1 may be involved in the pathogenesis of ED in patients without known CAD.Kobat MA, Fırdolas F, Balin M, Çelik A, Bentli R, and Baydas A. Circulating soluble lectin‐like oxidized low‐density lipoprotein receptor‐1 levels are associated with erectile dysfunction in patients without known coronary artery disease. J Sex Med 2013;10:2782–2789.